LATARJET PROCEDURE ON ANTERIOR SHOULDER INSTABILITY IN PROFESSIONAL SOCCER PLAYERS - STIRMA, GUILHERME AUGUSTO (Acta Ortop Bras, 2020)
Anterior glenohumeral instability is a frequent cause of professional soccer players’ removal, reduced performance, and prolonged recovery. Players are subjected to intense physical contact and high performance, thus demanding lower rates of recurrence after surgical correction so they can return to sport quickly. OBJECTIVE: To assess professional soccer players treated by the Lartajet technique considering the rate and time of return to sports activities, complications or failures. METHODS: Analysis held between 2010 and 2018 of professional soccer players diagnosed with anterior shoulder instability operated by the open procedure of Lartajet in our service. RESULTS: The mean return to professional sports was 93.5 days. The mean time of surgery in relation to the first dislocation was 12.4 months. Each athlete had 4.3 shoulder dislocations until the procedure was performed. The rate of recurrence was zero and subluxation was not observed. CONCLUSION: The Latarjet procedure allowed all professional athletes to return to competitive activities quickly, without dislocations and subluxation, negative seizure and without complications during follow-up. Level of evidence IV, Case series.